Teaching in the time of COVID-19: A biological systems theory approach - Brigandi, Carla B.; Spillane, Nancy K.; Rambo-Hernandez, Karen E.; Stone, Jana (Frontiers in Education, 2022)
Abstract In 2020, schools around the U.S. and globally closed to in-person instruction in response to the COVID-19 pandemic. This study, embedded in ongoing research supported by a U.S. Department of Education Jacob K. Javits Gifted and Talented Education Award, investigated changes in roles, relationships, and educational activities resulting from the pandemic as perceived by educators in one rural and low SES Appalachian primary school. Using Bronfenbrenner’s (1977, 1979, & 2001) Bioecological Theory of Human Development, this study examined instructional modifications (proximal processes) resulting from the pandemic (chronosystem) in the school and home (microsystem context) and the development of teachers, parents, and students (persons) in response to those changes. Open-ended survey data were collected pre- and post-pandemic onset. Results indicated teachers perceived the pandemic as influencing what they taught, how they taught, and the roles of and relationships between teachers, parents, and students. Teachers adapted to the changing educational environment developing proficiency in online tools and skills to enhance communication. Parents assumed a more prominent role in their K-2 student’s schooling to ensure students logged in and were active online, paid attention while in class, and completed their assignments at home. These remote learning environments, which naturally distanced teachers from their students, coupled with uncertain parental involvement, challenged teachers in their formative assessments of student knowledge. While some students thrived with increased support from attentive parents—many students, particularly those already at-risk or in homes where internet or parental support were lacking—were adversely affected, thus widening the achievement gap.